2011
DOI: 10.1530/jme-11-0082
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to high fatty acids impedes receptor agonist-induced nitric oxide production and increments of cytosolic Ca2+ levels in endothelial cells

Abstract: Dyslipidemia is a common metabolic disorder in diabetes. Nitric oxide (NO) production from endothelium plays the primary role in endothelium-mediated vascular relaxation and other endothelial functions. Therefore, we investigated the effects of elevated free fatty acids (FFA) on the stimulation of NO production by phospholipase C (PLC)-activating receptor agonists (potent physiological endothelium-dependent vasodilators) and defined the possible alterations of signaling pathways implicated in this scenario. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…gene modification of the Ca 2+ handling machinery might recorrect the well known EPC dysfunctions that occur in patients affected by cardiovascular pathologies and hamper autologous cell transplantation. For instance, SOCE is up-regulated in bovine aortic ECs exposed to high glucose levels [138], whereas it is significantly decreased in ECs cultured in the presence of high concentrations of a mixture of fatty acids (oleate and palmitate) [139]. EPCs isolated from either diabetic or obese patients display reduced proliferative potential and migratory function.…”
Section: Store-operated Ca 2+ Entry As a Putative Tar-get Of Regeneramentioning
confidence: 99%
“…gene modification of the Ca 2+ handling machinery might recorrect the well known EPC dysfunctions that occur in patients affected by cardiovascular pathologies and hamper autologous cell transplantation. For instance, SOCE is up-regulated in bovine aortic ECs exposed to high glucose levels [138], whereas it is significantly decreased in ECs cultured in the presence of high concentrations of a mixture of fatty acids (oleate and palmitate) [139]. EPCs isolated from either diabetic or obese patients display reduced proliferative potential and migratory function.…”
Section: Store-operated Ca 2+ Entry As a Putative Tar-get Of Regeneramentioning
confidence: 99%
“…[24] Kim et al showed that each of these fatty acids impair basal and insulin-stimulated NO production in bovine aortic endothelial cells (BAECs), with palmitic acid exerting the greatest effect [25]. Elevated FFAs can promote de novo synthesis of diacylglycerol which activates certain protein kinase C (PKC) isoforms[7;16]. Tang and Li [16] reported that endothelial cells exposed to 5 or 10 days of palmitate treatment displayed impaired agonist-evoked (i.e., bradykinin, ATP) NO production that was secondary to blunted elevations of intracellular free Ca 2+ [Ca 2+ ]i. Co-culture of endothelial cells with PKC inhibitors neutralized the ability of palmitate to lower NO.…”
Section: Lipotoxicitymentioning
confidence: 99%
“…Elevated FFAs can promote de novo synthesis of diacylglycerol which activates certain protein kinase C (PKC) isoforms[7;16]. Tang and Li [16] reported that endothelial cells exposed to 5 or 10 days of palmitate treatment displayed impaired agonist-evoked (i.e., bradykinin, ATP) NO production that was secondary to blunted elevations of intracellular free Ca 2+ [Ca 2+ ]i. Co-culture of endothelial cells with PKC inhibitors neutralized the ability of palmitate to lower NO. This finding is consistent with observations that PKC activation selectively inhibits PI3K / Akt signaling in the vasculature [10;26] such that cGMP formation - an estimate of NO bioavailability – is impaired [27].…”
Section: Lipotoxicitymentioning
confidence: 99%
“…Excessive free fatty acids (FFAs) can promote de novo synthesis of diacylglycerol that activates classic and novel protein kinase C (PKC) isoforms [5, 6]. PKC activation inhibits insulin and Vascular endothelial growth factor (VEGF)-mediated activation of PI3K and Akt [7, 2••], which limits cGMP formation from nitric oxide (eNOS generated) activation of guanylate cyclase [8•].…”
Section: Part 1 Lipotoxicity and Vascular Dysfunctionmentioning
confidence: 99%